2019
DOI: 10.1186/s13018-019-1153-6
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma versus lidocaine as tenotomy adjuvants in people with elbow epicondylopathy: a randomized controlled trial

Abstract: Objectives To determine the efficacy of platelet-rich plasma (PRP) compared to lidocaine as a tenotomy adjuvant for people with elbow tendinopathy. Methods Our study was a parallel-group, double-blind, randomized trial involving 71 patients with recalcitrant elbow tendinopathy who received two sessions of ultrasound-guided tenotomy with either PRP or lidocaine in a tertiary public hospital. The primary end point was the percentage of patients with an improvement exceedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Rather, the efficacy of PRP in addition to tendon fenestration compared to tendon fenestration alone remains controversial. Martin et al [14] found in a partially blinded randomized controlled trial (RCT) involving 71 patients no clinical differences at 6 months of follow-up between 2 sessions of fenestration with either saline + local anesthetic or PRP + local anesthetic. In a similar blinded RCT involving 50 patients, Schöffl et al [15] found no clinical differences at 6 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, the efficacy of PRP in addition to tendon fenestration compared to tendon fenestration alone remains controversial. Martin et al [14] found in a partially blinded randomized controlled trial (RCT) involving 71 patients no clinical differences at 6 months of follow-up between 2 sessions of fenestration with either saline + local anesthetic or PRP + local anesthetic. In a similar blinded RCT involving 50 patients, Schöffl et al [15] found no clinical differences at 6 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential benefits of PRP are discordant, especially concerning the elbow. Even if the superiority of PRP over corticosteroids is well established [13], the efficacy of PRP in addition to tendon needling or fenestration compared to tendon needling or fenestration alone is still controversial [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Rather, the e cacy of PRP in addition to tendon fenestration compared to tendon fenestration alone remains controversial. Martin et al (14) found in a partially blinded randomized controlled trial (RCT) involving 71 patients, no clinical differences at 6 months of follow-up between 2 sessions of fenestration with either saline + local anesthetic or PRP + local anesthetic. In a similar blinded RCT involving 50 patients, Schö et al (15) found no clinical differences at 6 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential bene ts of PRP are discordant, especially concerning the elbow. Even if the superiority of PRP over corticosteroids is well established (13), the e cacy of PRP in addition to tendon needling or fenestration compared to tendon needling or fenestration alone is still controversial (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Even if the superiority of PRP over corticosteroids is well established (13), the superiority of PRP on tendon needling or peppering is still controversial. Martin et al (14) found in a partially blinded randomized controlled trial (RCT) involving 71 patients no clinical differences at 6 months of follow-up between 2 sessions of peppering with saline + local anesthetic and PRP + local anesthetic. In a similar blinded RCT involving 50 patients, Schö et al (15) found no clinical differences at 6 months of follow-up.…”
Section: Introductionmentioning
confidence: 99%